2022
DOI: 10.3389/fmars.2022.981365
|View full text |Cite
|
Sign up to set email alerts
|

Cellular disturbance and thermal stress response in mussels exposed to synthetic and natural microfibers

Abstract: Textile microfibers (MFs) have natural (e.g. cotton, wool and silk) or synthetic origin (e.g. polyester and polyamide), and are increasingly documented in the marine environment. Knowledge on their biological effects in marine organisms is still limited, and virtually unexplored is their capability to modulate the responsiveness toward other stressors, including those of emerging relevance under global changes scenario. With such background, the aims of this study were to i) determine the ingestion and biologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…47 In farmed mussels from the Mediterranean Sea M. galloprovincialis, synthetic and natural textile microfibers (an average of 14.5720 microfibres per individual) have been documented with cotton and wool as the majority (54% and 985.14 μm in length), raising concerns owing to recent reports on neurotoxicity, oxidative stress and metabolic and developmental disorders. 48,49 To date, no information is available on the effects of nanoscale natural fibers although fragmentation below 100 nm could naturally occur and is more likely in areas receiving higher amounts, such as along marine coasts. To fill such a knowledge gap, herein, we investigate the uptake and biological effects of NC fibers in the marine mussel M. galloprovincialis through an acute in vivo exposure (96 h uptake; 48 h effects) using synthesized CNF and TOCNF in two concentrations: a) 1 μg L −1 in the range of Predicted Environmental Concentrations (PEC, 0.23-2.37 μg L −1 in 2025 by Stoudmann et al 24 ) and b) 1 mg L…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…47 In farmed mussels from the Mediterranean Sea M. galloprovincialis, synthetic and natural textile microfibers (an average of 14.5720 microfibres per individual) have been documented with cotton and wool as the majority (54% and 985.14 μm in length), raising concerns owing to recent reports on neurotoxicity, oxidative stress and metabolic and developmental disorders. 48,49 To date, no information is available on the effects of nanoscale natural fibers although fragmentation below 100 nm could naturally occur and is more likely in areas receiving higher amounts, such as along marine coasts. To fill such a knowledge gap, herein, we investigate the uptake and biological effects of NC fibers in the marine mussel M. galloprovincialis through an acute in vivo exposure (96 h uptake; 48 h effects) using synthesized CNF and TOCNF in two concentrations: a) 1 μg L −1 in the range of Predicted Environmental Concentrations (PEC, 0.23-2.37 μg L −1 in 2025 by Stoudmann et al 24 ) and b) 1 mg L…”
Section: Introductionmentioning
confidence: 99%
“…In farmed mussels from the Mediterranean Sea M. galloprovincialis , synthetic and natural textile microfibers (an average of 14.5720 microfibres per individual) have been documented with cotton and wool as the majority (54% and 985.14 μm in length), raising concerns owing to recent reports on neurotoxicity, oxidative stress and metabolic and developmental disorders. 48,49…”
Section: Introductionmentioning
confidence: 99%
“…[52][53][54][55][56], including plastics, e.g. [31,[57][58][59], have previously been documented in mussels under conditions of immersion. This present work, however, provides the first evidence of an enhanced thermal mortality through an exposure to microplastic leachates.…”
Section: Discussionmentioning
confidence: 99%
“…Microfiber ingestion in oysters and mussels may negatively affect shellfishes' reproductive output [53]. Mytilus galloprovincialis exposed to synthetic and natural microfibers resulted in different magnitudes of biological disturbance, depending on the nature of the microfiber [54]. Watts et al [55] reported reductions in food consumption and in energy available for growth of the shore crab Carcinus maenas due to microfiber exposure.…”
Section: Microfiber Pollution In the Marine Environmentmentioning
confidence: 99%